Pembuatan Tepung Jagung Kuning Pramasak dengan Proses Nixtamalisasi serta Karakterisasi Produknya - Bangun P Nusantoro; Haryadi Haryadi; Nursigit Bintoro; Purnama Darmadji (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2005)
The nixtamalization process of maize is an ancient alkaline-temperature process commonly used in the production of maize-related food products. Whole maize grains are heated in a cooker with an alkaline solution. Then the cooked grains are washed with hot tap water and rested for a while to assure a better distribution of moisture within the maize grains. Unfortunately this nixtamalized maize is not done yet. This research investigates the appropriate cooking time and concentration of alkaline solution. Visual assessment, hardness and lightly to flatten on cooked grains are basis of decision. Afterward, the cooked grains are flattened into chips which could be function as by product. Instant corn flour is obtained by grounding dry chips with a hammer mill. Finally, chemical compositions and physicochemical properties of instant cornflour are evaluated to measure its quality. The nixtamalized maize was done after cooking in 90 minutes at 3%w/w Ca(OH)7 solution and yielded 89% instant corn flour. Resulted corn flour had moisture (10,67%), crude protein (9,15%), crude lipid (5,40%), ash (2,55%) and amylose (26,24%). The resulted data of physicochemical properties showed that instant corn flour had colour (L 84,23; a -0,12; b +24,50), bulk density (606 kg/m3), angle of repose (36,49Â°), swelling power (7,03 g/g), water holding capacity (617%) and digestibility 58,69% in 6 hours.